Predation risk and the evolution of a vertebrate stress response: Parallel evolution of stress reactivity and sexual dimorphism. (12th September 2021) - Vinterstare, Jerker; Ekelund Ugge, Gustaf M. O.; Hulthén, Kaj; Hegg, Alexander; Brönmark, Christer; Nilsson, Per Anders; Zellmer, Ursula Ronja; Lee, Marcus; Pärssinen, Varpu; Sha, Yongcui; Björnerås, Caroline; Zhang, Huan; et al.
Abstract: Predation risk is often invoked to explain variation in stress responses. Yet, the answers to several key questions remain elusive, including the following: (1) how predation risk influences the evolution of stress phenotypes, (2) the relative importance of environmental versus genetic factors in stress reactivity and (3) sexual dimorphism in stress physiology. To address these questions, we explored variation in stress reactivity (ventilation frequency) in a post‐Pleistocene radiation of live‐bearing fish, where Bahamas mosquitofish ( Gambusia hubbsi ) inhabit isolated blue holes that differ in predation risk. Individuals of populations coexisting with predators exhibited similar, relatively low stress reactivity as compared to low‐predation populations. We suggest that this dampened stress reactivity has evolved to reduce energy expenditure in environments with frequent and intense stressors, such as piscivorous fish. Importantly, the magnitude of stress responses exhibited by fish from high‐predation sites in the wild changed very little after two generations of laboratory rearing in the absence of predators. By comparison, low‐predation populations exhibited greater among‐population variation and larger changes subsequent to laboratory rearing. These low‐predation populations appear to have evolved more dampened stress responses in blue holes with lower food availability. Moreover, females showed a lower ventilation frequency, and this sexual dimorphism was stronger in high‐predation populations. This may reflect a greater premium placed on energy efficiency in live‐bearing females, especially under high‐predation risk where females show higher fecundities. Altogether, by demonstrating parallel adaptive divergence in stress reactivity, we highlight how energetic trade‐offs may mould the evolution of the vertebrate stress response under varying predation risk and resource availability. Abstract : Predictions for the evolution of the stress response under varying intensity and frequency of stressful encounters inenvironments with (A) low food availability and (B) high food availability based on our simple conceptual model that assumes its evolution depends solely on selection from these three factors (see text, supplementary material; 0.1 and 1.0 food levels depicted; full range of frequency of stressful encounters depicted; intensity of stressful encounters range from 0.25 to 1.0). Approximate regions for each predation regime for Bahamas mosquitofish denoted with LP (low predation) and HP (high predation).